Mudanças evolutivas nas curvas de normas de reação térmica avaliadas pela depleção do amido armazenado nas células do parênquima radial - Abreu Júnior, Áureo Aparecido (2016)
A simple method to conduce a relationship between physiological responses of plants and thermal stresses is by quantifying the number of parenchyma cells with remaining starch, which are depolymerized and transformed in simple sugars and move towards embolized vessels in order to refill them. The knowledge from the dynamic of this depletion can be achieved by using statistical models such as thermal performance curves (TPC). The aim of this study was to quantify radial parenchyma cells with residual starch storages in order to evaluate changes in TPC in response to increases in temperature in seedlings of Toona ciliata, in different treatments of combining time and temperature, therefore to evaluate variations in the TPC and to understand whether these changes are over genetic and inherit control. We used a protocol of heat induced in the stems of the seedlings, anatomical cuts and staining with neutral red for the clone BV1120, which was used as model to fit polynomial curves of TPC. After these mathematical fits and validation of these models with lignotubers from the specie Eucalyptus urophylla, we defined a depletion time of 50% (td50) from the starch storage for each thermal treatment, so we could compare the performance for the others five clones: BV1110, BV1121, BV1151, BV1210 and BV1321. The R2 values were all above 85%. Results indicated that clone BV1110 had the biggest starch storage in all thermal treatments, in contrast to the clone BV1210 that had the lowest values for starch storage. The variation of the starch content is highly heritable and it shows that genes, which have the control of this feature, are already fixed in the population. Thus, selections can improve the tolerance of theses clones to temperature alterations on the environment.